Analysis of Social Support on the Decision to Continue Higher Education: A Literature Review - Liubana, Alfred; Kurjono, Kurjono; Ahman, Eeng; Kurniawati, Susanti (Lectura : Jurnal Pendidikan, 2025)
Education is important in human life because it helps people build strong character and morality, helping them to distinguish between what is right and wrong. This research aims to determine what forms of social support exist, what the role of social support is, and what the causes of low decision-making are in continuing higher education in Indonesia. This type of research used a systematic analysis of literature review. In refining the data that has been collected, the researcher identified, filtered, feasibility and clarified the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The data in this study were secondary data from 2020-2024 obtained from data Dimensions and Google Scholar. The results showed that 1) Forms of social support in the findings come from peers, parental motivation, parental support, family economic status, parental education, social environment, counselling guidance and homeroom teacher, facilities and infrastructure; 2) with the existence of social support for the decision to continue higher education, each individual received a more decent education, promising work, continued to exist in society, extended family assistance, and shaped the character and morals of the person, parental economic support was not one of the obstacles in continuing higher education due to the availability of scholarships; 3) The causes of the low decision to continue higher education were from internal and external factors. It can be concluded that understanding the many forms of social support and tackling the barriers to educational advancement are critical for increasing access to higher education.